2021
DOI: 10.1038/s41598-021-83055-w
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of obesity and an interrogation of the correlation between anthropometric indices and blood pressures in urban Lagos, Nigeria

Abstract: Adverse cardiovascular outcomes are linked to higher burden of obesity and hypertension. We conducted a secondary analysis of data for 5135 participants aged ≥ 16 years from our community-based hypertension prevalence study to determine the prevalence of obesity and association between multiple anthropometric indices and blood pressure (BP). The indices were waist circumference (WC), body mass index (BMI), waist-to-height ratio (WHtR), waist-to-hip ratio (WHR), a body shape index(ABSI), abdominal volume index … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
32
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 61 publications
8
32
1
Order By: Relevance
“…Similarly, significant differences were found among women who were obese, with socio-demographic factors, such as increasing age (40–44 years; 45–49 years), higher education, employed, higher wealth index, married/widowed, regional differences (South east, South south, and South west zones), height above average, weight above average, having more than four children, contraceptive use (traditional/modern), and cigarette smoking. Several studies (cross-sectional and longitudinal) have demonstrated the influence of socio-demographic factors with studies from sub-Saharan Africa [ 1 , 2 , 67 ], and this is consistent with findings from studies conducted in Nigeria [ 9 , 13 , 22 ].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Similarly, significant differences were found among women who were obese, with socio-demographic factors, such as increasing age (40–44 years; 45–49 years), higher education, employed, higher wealth index, married/widowed, regional differences (South east, South south, and South west zones), height above average, weight above average, having more than four children, contraceptive use (traditional/modern), and cigarette smoking. Several studies (cross-sectional and longitudinal) have demonstrated the influence of socio-demographic factors with studies from sub-Saharan Africa [ 1 , 2 , 67 ], and this is consistent with findings from studies conducted in Nigeria [ 9 , 13 , 22 ].…”
Section: Discussionsupporting
confidence: 85%
“…In South Africa, malnutrition has become an emergent public health problem, as the country is going through an epidemiological health transition revealing prevailing chronic malnutrition [ 12 ]. Factors such as increased adoption of more westernized diets and the rise in sedentary behavior, owing to modernization, improved transport systems, and easy convenient access to unhealthy fast foods, are associated with over-weight/obesity and its related-health problems in South Africa [ 6 , 13 ]. Studies have documented that the body mass index (BMI) cutoffs for women and men are 29.2 and 23.6 respectively, whereby 68% of women are overweight/obese while 3% are underweight, as two-thirds of women (59%) have a BMI in the standard range [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Globally, there has been an increased intake of energy-dense foods that are high in fat and sugars and an increase in physical inactivity due to the increasingly sedentary nature of many forms of work, changing modes of transportation, and increasing urbanization. Overweight is a known risk factor for non communicable diseases (NCDs) and is an important issue to address in NCD prevention [46][47][48][49][50][51] especially in Nigeria where the prevalence rate of overweight individuals ranged from 20.3%-35.1%. [47][48][49] Furthermore, the mean SBP, DBP and microalbumin (µalb) levels were not significantly different when compared between the male and female HIV seronegative participants respectively, although plasma creatinine level was significantly higher in the male HIV seronegative participants than in the female HIV seronegatives.…”
Section: Discussionmentioning
confidence: 99%
“…Overweight is a known risk factor for non communicable diseases (NCDs) and is an important issue to address in NCD prevention [46][47][48][49][50][51] especially in Nigeria where the prevalence rate of overweight individuals ranged from 20.3%-35.1%. [47][48][49] Furthermore, the mean SBP, DBP and microalbumin (µalb) levels were not significantly different when compared between the male and female HIV seronegative participants respectively, although plasma creatinine level was significantly higher in the male HIV seronegative participants than in the female HIV seronegatives. it is a known factor that there is a gender based disparity in plasma creatinine level as a result of differences in muscle mass which is usually higher in men than in women.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiovascular disease including hypertension is one of the commonest noncommunicable diseases in the African population ( 10 ). Diabetes and obesity are increasingly emerging as important chronic illnesses in African populations ( 11 ). Each of these places individuals at increased risk for developing severe COVID-19.…”
Section: Adult Lung Health In Africa In the Context Of Covid-19mentioning
confidence: 99%